Perancangan dan Implementasi Sistem Pemantauan Suhu dan Ketinggian Air pada Akuarium Ikan Hias berbasis IoT - Piter Wijaya; Theophilus Wellem (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Environmental monitoring and control systems of various electronic equipment such as sensors, actuators, televisions, lights, and surveillance cameras are one of the essential applications of Internet-of-Things (IoT). The utilization of IoT has also given birth to the smart home concept, which is realized in the form of home automation, where various equipment at home is equipped with a microcontroller and WiFi module such that they can connect to the Internet and interact with each other. One of the equipment at home that can be monitored and controlled using IoT technology is a fish aquarium which is commonly owned by ornamental fish cultivators or people who have a hobby of taking care of ornamental fish. Taking care of ornamental fish requires special attention to the parameters of temperature and water quality such that the fish can grow well. This study aims to design and implement an IoT-based temperature and water level monitoring system in an aquarium. The hardware in this system is implemented using NodeMCU ESP8266 as the central controller and the WiFi module that connects the system to the Internet, temperature sensor DS18B20, ultrasonic sensor HC-SR04, and relays to turn on and off equipment controlled by the system. In addition, Telegram bots are used to give commands to control equipment and receive notifications from the system. The testing results show that the designed system can work according to predetermined specifications. If the water temperature in the aquarium is outside of a specified range (24°C to 32°C), the system will activate a fan or a heater to adjust the water temperature.